(untitled) (Health and Biosciences, 2025)
Anatomists in Nigeria continue to be perceived primarily as educators and custodians of cadavers—roles rooted in colonial medical traditions. This limited view has obscured the wider relevance of anatomical science in national development. In contrast, global practice now positions Anatomists as integral contributors to surgical training, forensic investigation, biomedical innovation, and public-health research. This paper, titled Repositioning Anatomists in Nigeria for National Development: Challenges and Policy Perspectives, Beyond the Morgue and Classroom, critically examines the socio-institutional and legal factors that confine Nigerian Anatomists to narrow professional roles. It adopts a narrative literature review and policy-analysis approach to evaluate global best practices, identify structural barriers, and propose actionable reforms for Nigeria. Key findings reveal persistent stereotypes, outdated curricula, inadequate policy recognition, and the continued enforcement of the obsolete Anatomy Act 1933, while the proposed Anatomy Bill 2021, which would empower Anatomists through professional regulation and broader practice rights remains unpassed. The paper calls for curriculum modernization, policy advocacy, interprofessional collaboration, and the establishment of a functional Anatomy Council of Nigeria. Repositioning the discipline beyond the morgue and classroom is essential for integrating Anatomists into clinical, forensic, research, and technological sectors. Doing so will not only elevate the profession but also strengthen Nigeria’s healthcare, innovation, and scientific-development capacity for the 21st century.